Ideal Host for Digital Marketing: A Multi Criterion Decision Model Approach - Anoop Kumar Paul, Siddharth Kumar Bhoi, Prof. Vandana Srivasthva, Dr. Lakshmi. P (International Journal of Advanced Science and Technology, 2020)
The study  provides the outline of the basics of digital marketing to understand the behaviour of business organisation towards the online marketing and identifying the parameters to select the ideal host. An ideal host provide a wide range of choice under the budget that best suit for the organisation and efficiently reach to the customers, choosing the best host can achieve goals of the business. Effectiveness of a digital host depends upon the flexibility towards meeting clients’ needs and launching a user-friendly website that can attract visitors and making a strong web presence. The source of data collection used in the research was primary data which was gathered from sample size of 100 respondents and they were business organizations, start-ups and business agency of Bangalore. This paper is directed towards the previous study done on digital marketing. There are many research papers that doesn’t illustrate about choosing an ideal host on basis of reliability, flexibility, and suitability as per client’s need, many previous papers haven’t discussed about measuring the success of digital marketing. There are several types of cyber security challenges that has come up such as malware, cyber security issues that can adversely affect the growth of business, selection of a protective digital host is very important because it involves lot of sensitive customers data. This research paper points towards the gaps determined and bridging them and this shows the originality in this paper. The inferences from the data reveals that there are few attributes that needed to be considered while choosing the ideal  host for the digital marketing i.e. numbers of employee work in a hosting firm, how was their performance in recent years and how effective they are in attracting visitors to client’s website , analysing these attributes will draw a general characterises about a  web hosting service provider. Based on these features a client can make decision on choosing the best platform for digital marketing. The future of digital marketing depends on the way the marketers blend the traditional and modern media suiting the environment and present requirements of the customer.